<h3>
Answer: Choice C</h3>
Explanation:
In this answer choice, we effectively have two columns. In the first column is simply R and B, with R over B. This represents spinning either red (R) or blue (B).
Depending on the outcome, you branch the same outcomes from that.
So if you spin R, then you'll have R and B branch off that. Same idea applies to blue as well.
Something like choice D doesn't work because we have R show up twice at the very bottom.
let's first off take a look at the <u>tickmarks</u>, three <u>side tickmarks</u>, so all those 3 sides are equal, all have a length of y - 25, so is an equilateral triangle.
there are two <u>angle tickmarks</u>, meaning those two angles are equal, wait a second! if those two angles are equal, that means is an isosceles triangle.
now, in an equilateral triangle, all sides are equal, but also all angles are equal, since the sum of all interior angles is 180°, then each angle is really 60°.
let's notice that angle on the upper-left-corner, is a right-angle, but 60° are on the equilateral triangle, and so the remaining 30° must be on the isosceles triangle.
the isosceles triangle has then a vertex of 30°, and twin angles, the twin angles let's say are each a° so then
30° + a° + a° = 180°
30 + 2a = 180
2a = 150
a = 75° = y
now, let's recall, the isosceles triangle has twin angles but it also has twin sides, so the side "x" and the side with the tickmark are equal.
well, we know that y = 75, so the sides with the tickmark are then (75) - 25 = 50 = x.
First of all u draw a number line, then u labbel it, then go to zero, n count 6 negative steps, ok in simple terms move backwards thrice
Answer:
51
Step-by-step explanation:
Answer:
( f h ) (x) = 6 x² - 1
Step-by-step explanation:
<u><em>Step(i)</em></u>:-
Given<em> f(x) = 3 x - 4</em>
g (x) = −x²+2 x−5
<em> h (x) = 2 x² + 1</em>
j (x) = 6 x + 2 - 8 x
K (x) = 3 x² - x + 7
<u><em>Step(ii)</em></u>:-
<em>( f h ) (x) = f ( h (x)) = f ( 2 x² + 1 )</em>
= 3 (2 x² + 1 ) - 4
= 3 ((2 x² ) + 3 - 4
= <em>6 x² - 1</em>
<u><em> Final answer:</em></u>-
∴ <em> ( f h ) (x) = 6 x² - 1</em>